Faktor-faktor yang Mempengaruhi Produktivitas Kerja Karyawan Pada KPKNL Kota Pekalongan - Adiwijaya, Edwin Perdana (Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to determine the factors that affect employee productivity. The research was conducted at the Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) in Pekalongan City. The research respondents were 32 KPKNL employees taken based on the survey method using a questionnaire instrument. Data analysis using Multiple Linear Regression. The results showed that the training and skills variables positively affected work productivity, while motivation did not affect work productivity.